2016
DOI: 10.1038/srep32033
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Photoluminescence Thermal Quenching: Guidance for the Design of Highly Effective p-type Doping of Nitrides

Abstract: A contact-free diagnostic technique for examining position of the impurity energy level of p-type dopants in nitride semiconductors was proposed based on photoluminescence thermal quenching. The Mg ionization energy was extracted by the phenomenological rate-equation model we developed. The diagnostic technique and analysis model reported here are priorities for the design of highly effective p-doping of nitrides and could also be used to explain the abnormal and seldom analyzed low characteristic temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 25 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…These features are also evident in Figures a,c and a and are discussed comprehensively below. As the lattice temperature increases, the contribution from many of these states (transitions) decreases, as photogenerated carriers are able to redistribute among the various associated energy levels via thermal processes. …”
Section: Experimental Results and Analysismentioning
confidence: 99%
“…These features are also evident in Figures a,c and a and are discussed comprehensively below. As the lattice temperature increases, the contribution from many of these states (transitions) decreases, as photogenerated carriers are able to redistribute among the various associated energy levels via thermal processes. …”
Section: Experimental Results and Analysismentioning
confidence: 99%
“…However, the PL intensity of MI 3 -doped B-γ phases decreases significantly with higher doping concentration; 0.1 mol % SbI 3 - and BiI 3 -doped samples exhibit considerably suppressed PL signals at λ max of 933 and 930 nm (Figure S13a), respectively, and those with 3 mol % dopants emit almost negligible PL. To observe the PL signal of MI 3 -doped B-γ phases by eliminating the thermal quenching effect, the measurement temperature was lowered to 100 K. The 3 mol % SbI 3 - and BiI 3 -doped samples exhibit a weak PL at λ max of 955 and 953 nm, respectively, at 100 K, which is slightly red-shifted from those at RT (Figure S13b). This difference is attributed to the temperature-dependent emission behavior of B-γ CsSnI 3 as reported previously .…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that the polarization-induced three-dimensional hole gas (3DHG) that is obtained by grading the Al composition in the AlGaN layer can enable a higher hole concentration. The polarization-induced-doping design numerically proves to be effective in facilitating the hole injection capability for the DUV LED, which has been reported by Chang et al In addition, the hole concentration for the p-type hole injection layer can also be increased by doping the last quantum barrier with Mg dopants, , such that the Mg dopants in Mg-doped last quantum barrier can be more efficiently ionized by the polarization induced electric field, while the built-in electric field can deplete the holes and the holes are finally stored in the p-type hole injection layer. It is reported that the activation energy of Mg dopants for the GaN film can be even lower than 100 meV by adopting the Mg–In codoping technology, by means of which the hole concentration can be increased to the order of 10 18 cm –3 . , Besides increasing the hole concentration for the p-type hole injection layer, another approach to boost the hole injection into the quantum well region is to energize holes, which is very helpful to facilitate the thermionic emission for holes to cross over the p-type electron blocking layer (p-EBL). On the other hand, the optical power for DUV LEDs can be further enhanced if the hole blocking effect by the p-EBL is minimized.…”
mentioning
confidence: 99%
“…It is reported that the activation energy of Mg dopants for the GaN film can be even lower than 100 meV by adopting the Mg−In codoping technology, by means of which the hole concentration can be increased to the order of 10 18 cm −3 . 10,11 Besides increasing the hole concentration for the p-type hole injection layer, another approach to boost the hole injection into the quantum well region is to energize holes, 12 which is very helpful to facilitate the thermionic emission for holes to cross over the p-type electron blocking layer (p-EBL). On the other hand, the optical power for DUV LEDs can be further enhanced if the hole blocking effect by the p-EBL is minimized.…”
mentioning
confidence: 99%